Experimental and numerical heat transfer investigation of reverse jet impingement - Ahmed, Abdallah (2023)
This project aimed to study heat transfer and flow in double wall aerofoil cooling using two primary studies: a novel jet impingement cooling geometry and a typical film cooling arrangement. Experimental testing with thermochromic liquid crystal validated numerical work using ANSYS Fluent. A novel ‘reverse’ jet impingement geometry was developed to enhance heat transfer performance, comprising of a ‘dimple’ target enclosed within a cylindrical ‘silo’. Experimental variations included Reynolds number range of 10,000 to 70,000, jet-to-target, crossflow condition, and an extended nozzle geometry. An overall enhancement of heat transfer was achieved with the novel geometry, with optimum jet to target spacing found at around 4 jet diameters, and some reduction in crossflow effects were observed. A numerical investigation validated against experimental data for a novel 'reverse' jet impingement geometry was conducted. Optimizations in jet-to-jet and jet-to-target spacing were found, but no significant optimization of inlet condition was observed. The effect of outlet condition on discharge coefficient was significant, with an optimum nozzle length of 1 jet diameter for heat transfer enhancement. Staggered and inline dimples were shown to provide similar enhancements to heat transfer, significantly compared to a traditional flat plate target. The study evaluated heat transfer and discharge coefficients in a scaled cylindrical film cooling channel with varied Reynolds number, entry sharpness, inclination, and rotation angle.